Decolonizing Indigenous education : an Amazigh/Berber ethnographic journey - Taieb, Si Belkacem (Palgrave Macmillan's postcolonial studies in education., 2014)
"In this work exploring the Kayble people of Algeria and their educational journeys, Si Belkacem Taieb explores an epistemological and ontological framework for Kayble education. He does so by undertaking a narrative inquiry: an auto-ethnographic journey, in which the journey of one's self and the journey of one's people are inextricably intertwined. In a postcolonial cultural journey in an Indigenous, North African Kayble landscape and the development of an Amazigh educational philosophy, Taieb writes the sociological foundations of an Amazigh educational system: one that removes Amazigh education from its colonial heritage and restores it to the people who create and use it"--